Short-term blood pressure variability - variation between arm side, body position and successive measurements: a population-based cohort study - Lacruz, Maria Elena; Kluttig, Alexander; Kuß, Oliver; Tiller, Daniel; Medenwald, Daniel; Nuding, Sebastian; Greiser, Karin Halina; Frantz, Stefan; Haerting, Johannes (BMC cardiovascular disorders, 2017)
(3–5) arm-side; Blood pressure variability; Body position; Hypertension; Successive measurements